Bolivia : Staff Assessment of Qualification for the Multilateral Debt Relief Initiative. (Policy Papers; Policy Paper, 2005)
Staff is of the view that all criteria have been met, and recommends that the Board determine that Bolivia qualifies for immediate debt relief under the MDRI.